DAKWAH DALAM PLURALISME BERAGAMA - Fifi Novianty (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2021)
This journal wants to explain about Da'wah in the midst of religious pluralism brought by KH.A Syatori at the Dar Al-Tauhid Arjawinangun Islamic Boarding School in Cirebon bringing positive positive social relations between students and the community, both Muslim and non-Muslim. In addition to focusing heavily on the process of learning the Qur'an, KH A Syatori also always informs students of the Dar Al-Tauhid Arjawinangun Islamic Boarding School to be interconnected between religious communities, while the religious environment of the students diverts this matter inseparable from the influence of education applied by KH. A Syatori The results of the study said that the figure who was the pioneer of Islamization in the midst of religious pluralism in the Dar Al-Tauhid Arjawinangun Islamic Boarding School was KH. A Syatori has proven to his people that Islam is a religion that will increase the level of understanding and can unite with other non-Muslims to create a beautiful religious harmony in the environment of Dar Al-Tauhid Arjawinangun Islamic Boarding School. And the da'wah pluralism has brought influence in the fields of Economy, Social, Politics, and Culture.